Outfitting the Office: An Experiential Health and Safety Exercise. (September 2019) - Robertson, Kirsten M.; Chase, Hayley; Castonguay, Arianna
We created the "Outfitting the Office" exercise to increase student engagement with health and safety concepts in introductory human resource management courses. The experiential exercise consists of two phases: (1) hazard recognition in a typical office and print room setting and (2) office design with a focus on employee health and wellness. The first phase was developed as an introductory activity to get students working together in their teams and to sensitize them to safety considerations. The second, longer, phase provides students with the opportunity to apply their readings in a decision-making scenario. In this scenario, students simulate a human resources firm that is tasked with renovating and furnishing a healthy and safe office space. Feedback from students indicates that this exercise is a fun and engaging way to learn about the health and safety factors that can affect worker comfort and enhance individual, team, and organizational productivity.